2022
DOI: 10.3390/foods11050710
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Preparation, Characterization, and Stability of Freeze-Dried Curcumin-Loaded Cochleates

Abstract: Curcumin (CUR), a polyphenolic substance extracted from plants, has extensive pharmacological activities. However, CUR is difficult to be absorbed in the body due to its poor stability and low solubility. Studies have found that cochleates can be used as a new delivery system to encapsulate bioactive agents for the purpose of improving its stability and bioavailability. In this study, thin-film dispersion and trapping methods were used to prepare curcumin-loaded cochleates (CUR-Cochs). Then CUR-Cochs were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In addition to their function in cell signaling pathways, ROS can control how cells behave [38]. For instance, too much ROS can result in DNA deterioration, protein malfunction, and lipid peroxidation, all of which can eventually cause cell death [40]. Additionally, knowing the regulatory mechanisms that regulate cells, ROS in particular locations within the cell is essential for figuring out their role in cell signaling [41].…”
Section: Cell Signaling Pathways In Ros Regulationmentioning
confidence: 99%
“…In addition to their function in cell signaling pathways, ROS can control how cells behave [38]. For instance, too much ROS can result in DNA deterioration, protein malfunction, and lipid peroxidation, all of which can eventually cause cell death [40]. Additionally, knowing the regulatory mechanisms that regulate cells, ROS in particular locations within the cell is essential for figuring out their role in cell signaling [41].…”
Section: Cell Signaling Pathways In Ros Regulationmentioning
confidence: 99%
“…However, it was suggested that the CUR-Cochs provided better stability than the CUR-Lipos in some harsh environments during the process and application. 35,39 3.4.5. Determination of the levels of MDA, LDH and SOD in cells.…”
Section: Papermentioning
confidence: 99%
“…The cell uptake efficiency as well as the mechanism of antioxidant were also investigated. 35 Hydrogen peroxide (H 2 O 2 ) was used to induce NIH3T3 cell damage, and an in vitro cell oxidative damage model was established. Then, the protective effect and related mechanisms of CUR-Cochs on NIH3T3 oxidative damage were explored.…”
Section: Introductionmentioning
confidence: 99%